Evaluation of chilling injury symptoms in bananas using optical imaging methods - Hashim, Norhashila (2012)
The development of chilling injury symptoms in bananas (Musa cavendishii) at different ripening stages (2 to 5) was investigated using optical imaging methods. A total of 240 bananas with 60 bananas per each ripening stage ripened in a commercial ripening room were stored at 6 and 13 °C for two days to induce chilling injury symptoms. Images of the bananas were acquired using RGB and backscattering imaging at before storage (T0),during storage i.e. after 24 hours of storage with 90-minute time intervals (T1 to T5) and after storage i.e. exposure to ambient temperatures with the same time interval (T6 to T10), to monitor the appearance of chilling injury symptoms. The captured colour images were analyzed and valuable information from the images was extracted. Backscattering images were acquired using laser diodes emitting at 660 nm (visible light) and 785 nm (near-infrared light) wavelengths. The backscattering images were analyzed based on the changes of intensity in the radial direction providing a curve of intensity, also known as the backscattering profile. The backscattering parameter such as inflection point (IP),slope after inflection point (SA), full width at half maximum (FWHM) and saturation radius (RSAT) were extracted from the backscattering profile to relate with the appearance of chilling injury symptoms. The changes in all the optical parameters as a function of time were investigated. The changes in colour parameters were compared with visual assessment (VA) values while the changes in backscattering parameters were compared with pigment and water contents. Since VA is a non-destructive method, the measurement was conducted immediately after measurements using optical imaging methods (T0 to T10). The pigment and water contents measurements, due to their destructive methods, were carried out at the end of the experiment (T10). Significant (P<0.05) changes in all optical parameters, VA, pigments and water content subjected to temperature, ripening stage and treatment time were obtained. The analysis of the changes in colour parameters during treatment time provided the onset values of colour and time for development of chilling injury. The rate of reaction for the colour changes during the appearance of chilling injury symptoms were investigated using zeroth, first- and second-order model. Results revealed that hue (H) was the most suitable colour parameters to evaluate the development of chilling injury symptoms. The changes in H during development of chilling injury symptoms for each ripening stage can be predicted using zeroth-order model and first-order model for during and after storage, respectively. For during storage, kinetic model for each ripening stage provided lower uncertainty than irrespective ripening stages with R≥0.970. For after storage, kinetic model irrespective ripening stages provided comparable results with each ripening stage with R varies from 0.936 to 0.979 for analysis with each ripening stage and R=0.976 for analysis irrespective ripening stages. Analysis of the changes in backscattering parameters revealed that backscattering imaging at 660 nm obtained lower uncertainty than 785 nm with misclassification error less than 7% for 660 nm and 20% for 785 nm. Results also revealed that FWHM and the combination of IP, SA and FWHM for 660 nm and 785 nm respectively were the most appropriate backscattering parameters for evaluating chilling injury. Hence, optical imaging methods i.e. RGB and backscattering imaging are potentially useful in the evaluation of chilling injury symptoms in bananas.